2004
DOI: 10.1038/sj.eye.6701633
|View full text |Cite
|
Sign up to set email alerts
|

Use of disposable prism tonometry in routine clinical practice

Abstract: Aim To establish the reliability, efficacy, and safety of disposable prism tonometry and validate its routine use for screening as well as monitoring of glaucoma. Methodology Intraocular pressure (IOP) of 400 eyes of 200 consecutive patients who attended the general ophthalmic clinic was checked with both the Goldmann applanation tonometer and a disposable tonometer prism by an experienced examiner after obtaining informed consent. The data were statistically analysed. Results The mean difference in the IOP be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…While our results were in line with those studies, we found some limitations in the study design, as these studies tested either Tonosafe 17 or Tonoshield 12 against the standard Goldmann applanation tonometry and they did not compare one prism vs the other. For this reason, we conducted a method analysis that compared three methods instead of two.…”
Section: Discussionsupporting
confidence: 89%
“…While our results were in line with those studies, we found some limitations in the study design, as these studies tested either Tonosafe 17 or Tonoshield 12 against the standard Goldmann applanation tonometry and they did not compare one prism vs the other. For this reason, we conducted a method analysis that compared three methods instead of two.…”
Section: Discussionsupporting
confidence: 89%
“…29 Unlike the disposable tonometer shield (eg Tonoshield TM ), disposable acrylic tonometer prisms (eg Tonosafe TM and Tonojet TM ) have been found to correlate well with standard Goldmann tonometry measurements in the general and emergency eye clinic setting. 30,31 However, a recent study has found the Tonosafe TM prism to be less accurate in a glaucoma population, particularly where the intraocular pressure exceeds 25 mm Hg. 32 Furthermore, the use of a disposable tonometer does not completely eliminate the risk of cross-contamination between eyes due to manual handling of the tonometer prism 33 and has cost implications.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, the use of a disposable tonometer does not completely eliminate the risk of cross-contamination between eyes due to manual handling of the tonometer prism 33 and has cost implications. 30 Currently, in the UK, there appears to be great disparity between current tonometer disinfection practice and published international recommendations, with some institutions using non-evidence-based practices, which may render patients susceptible to transmissible ocular infections and possibly systemic disease. This survey highlights the need for the development of tonometer disinfection guidelines in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [48][49][50] demonstrate the accuracy and reliability of disposable prism tonometry when compared to the gold standard of Goldmann tonometry. Inferences from these studies indicate within the advantages of disposable prisms, a short learning curve, ease of use, and reproducibility of results.…”
Section: Eyementioning
confidence: 99%